A retrospective and prospective look at strategies to increase adolescent HPV vaccine uptake in the United States - Katharine J. Head; Erika Biederman; Lynne A. Sturm; Gregory D. Zimet (Human Vaccines & Immunotherapeutics, 2018)
The HPV vaccine debuted more than ten years ago in the United States and many strategies have been evaluated to increase HPV vaccination rates, which include not only improving current vaccination behaviors but also sustaining these behaviors. Researchers and practitioners from a variety of backgrounds have engaged in this work, which has included efforts directed at public health and government policies, health education and health promotion programs, and clinical and patient-provider approaches, as well as work aimed to respond to and combat anti-HPV vaccination movements in society. Using a previously developed conceptual model to organize and summarize each of these areas, this paper also highlights the need for future HPV vaccine promotion work to adopt a multi-level and, when possible, integrated approach in order to maximize impact on vaccination rates.